Demonology, dark fantasy, and the devil: representations of early criminological theory and justice in Diablo 2 - Posick, Chad (Video games, crime and control, 2024)
Tristram is overtaken by evil. The hero of the land wanders off and falls into a deep depression and the only hope of bringing light back to society is up to the game player. Most of the evil taking over the land is related to possession from demons such as Baal, Mephisto, and Diablo. Like society before the Enlightenment, Diablo 2 suggests that evil is the basis for explaining bad behavior. It also suggests that the only response to evil behavior, aside from exorcism, is confinement (jail or dungeon). There is little law in Tristram and vigilantism is rampant. This chapter will use the gameplay of Diablo 2 to highlight pre-Enlightenment theories of crime and criminal justice which rely heavily on religious concepts and approaches to the explanation of antisocial behavior and societal response to that behavior.